ROLLE UND AUFGABEN DES CHEFTRAINERS IN DEN SPORTKLUBS UND IN DEN FUSSBALLKLUBS - Röder, H.; Briest, D.; Kadow, H.; Kötteritzsch, G.; Rabe, H. G.; Schröter, H. (Theorie und Praxis des Leistungssports, 1979)
REFERAT F3